A comprehensive review of factors affecting wellbore integrity in CO2 injection wells - Faysal Ahammad; Saman Azadbakht (Energy Geoscience)
The preservation of the integrity of CO2 injection wells holds immense significance for the efficacy of Carbon Capture and Storage (CCS) projects. This is attributable to the fact that a wellbore exhibiting robust mechanical and flow integrity substantially diminishes the likelihood of CO2 leakage into the overlying aquifer or release to the atmosphere, thereby curtailing associated risks. Given the potential hazards and repercussions stemming from the failure of CO2 injection wells, encompassing environmental catastrophes, financial implications, and health risks, it is imperative to earnestly address these challenges through adept management and monitoring protocols. This study aims to advance the current understanding and enhance the management of wellbore integrity issues in CO2 injection wells. Accordingly, this review paper undertakes a thorough exploration of the primary factors influencing wellbore integrity in CO2 injection wells. Furthermore, it delineates a pressing necessity for more exhaustive investigations regarding the influence of CO2 injection rate, CO2 purity, and wellbore geometry on wellbore integrity.